Учебно-методическое обоснование целесообразности внедрения телемедицинских технологий для лиц пожилого возраста в одесском регионе = Telemedical technologies implementation teaching and methodic reasonability background for aged people in Odessa region - Polyasny, V. A. (Journal of Education, Health and Sport, 2015)
Polyasny V. A. Учебно-методическое обоснование целесообразности внедрения телемедицинских технологий для лиц пожилого возраста в одесском регионе = Telemedical technologies implementation teaching and methodic reasonability background for aged people in Odessa region. Journal of Education, Health and Sport. 2015;5(8):353-359. ISSN 2391-8306. DOI10.5281/zenodo.29565 http://dx.doi.org/10.5281/zenodo.29565 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A353-359 https://pbn.nauka.gov.pl/works/614188 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.06.2015. Revised 24.08.2015. Accepted: 24.08.2015. УДК 681.317+ 61:621.397.13./398 УЧЕБНО-МЕТОДИЧЕСКОЕ ОБОСНОВАНИЕ ЦЕЛЕСООБРАЗНОСТИ внедрениЯ телемедицИНских технологий для лиц пожилого возраста в Одесском регионе TELEMEDICAL TECHNOLOGIES IMPLEMENTATION TEACHING AND METHODIC REASONABILITY BACKGROUND FOR AGED PEOPLE IN ODESSA REGION В. А. Полясный V. A. Polyasny Одесский национальный медицинский университет, Украина Odessa National Medical University, Ukraine Abstract On the basis of original results and data from literature the perspectives on exploration of ECG monitoring systems for patients suffered from heart and vessel diseases have been analyzed. Experiments were undertaken aimed for maintanence of stable and reliable telecommunicational connection in the city and rural zones. The character of connection from the mobile platform organized on the basis of ambulance has been also performed. The conclusion was made that monitoring systems as well as wireless communication – based telemedical consultations creates perspectives inOdessaregion. Key words: telemedicine, cardiologic telemedical devices, telemedical network. Резюме На основе собственных данных и данных литературы проанализированы возможности практического применения систем дистанционного мониторирования ЭКГ у пациентов с острыми заболеваниями сердечно-сосудистой системы. Проведены исследования с обеспечением устойчивой телекоммуникационной связи в условиях мегаполиса, а также сельской местности, при поддержке связи с мобильной платформой-автомобилем медицинской помощи. Сделан вывод о возможности эффективного мониторирования, телемедицинского консультирования кардиологических пациентов пожилого возраста с применением беспроводных систем связи в Одесском регионе. Ключовые слова: телемедицина, кардиологическое телемедицинское оборудование, телемедицинская сеть. Резюме НАВЧАЛЬНО-МЕТОДИЧНЕ ОБГРУНТУВАННЯ ДОЦІЛЬНОСТІ ВПРОВАДЖЕННЯ ТЕЛЕМЕДИЧНИХ ТЕХНОЛОГІЙ ДЛЯ ОСІБ ПОХИЛОГО ВІКУ В ОДЕСЬКОМУ РЕГІОНІ. На основі власних даних та даних літератури проаналізовано можливості практичного застосування систем дистанційного моніторування ЕКГ у пацієнтів з гострими захворюваннями серцево-судинної системи. Проведено дослідження із забезпеченням стійкого телекомунікаційного зв’язку в умовах мегаполісу, а також сільській місцевості, за підтримки зв'язку з мобільною платформою-автомобілем медичної допомоги. Зроблено висновок про можливість ефективного моніторування, телемедичного консультування кардіологічних пацієнтів похилого віку із застосуванням бездротових систем зв'язку в Одеському регіоні. Ключові слова: телемедицина, кардіологічне телемедичне устаткування, телемедична мережа.